Redefining Tropical Walkability: The Challenge of Thermal Comfort for Captive Pedestrians in ITERA - Elisabet Nungky Septania; Stirena Rossy Tamariska; Galuh Fajarwati; Rabita Akbari Sitompul; Adelia Enjelina Matondang; Rendy Perdana Khidmat (Jurnal Arsitektur, 2026)
University campuses in hot-humid tropical climates face complex challenges in balancing sustainability visions with user comfort. This study evaluates walkability at Institut Teknologi Sumatera (ITERA), a campus implementing vehicle restriction policies that effectively create a population of "captive pedestrians"dormitory residents with no alternative mode of transport. Utilizing a mixed-methods approach, the research analyzes perceptions from 108 respondents alongside field observations of seven primary pedestrian pathways. The findings indicate that thermal discomfort is the most critical barrier (accounting for 40.6% of complaints), signaling the inadequacy of current landscape designs in mitigating the tropical microclimate. Further analysis reveals spatial injustice, where the route with the highest user volume (Route 7) exhibits the most severe physical degradation, alongside significant gender disparities in safety perceptions. The study concludes that the success of Green Campus policies relies heavily on a paradigm shift from mere pavement provision to comprehensive climate protection. Recommendations emphasize the urgent need for constructing covered walkways and improving crossing facilities to ensure humane, safe, and climate-responsive mobility for the entire academic community.